Usefulness of three‐dimensional echocardiography in the assessment of valvular involvement in Loeffler endocarditis. Issue 7 (9th June 2017) - Hernandez, Carlos M.; Arisha, Mohammed J.; Ahmad, Amier; Oates, Ethan; Nanda, Navin C.; Nanda, Anil; Wasan, Anita; Caleti, Beda E.; Bernal, Cinthia L. P.; Gallardo, Sergio M.
Abstract : Loeffler endocarditis is a complication of hypereosinophilic syndrome resulting from eosinophilic infiltration of heart tissue. We report a case of Loeffler endocarditis in which three‐dimensional transthoracic and transesophageal echocardiography provided additional information to what was found by two‐dimensional transthoracic echocardiography alone. Our case illustrates the usefulness of combined two‐ and three‐dimensional echocardiography in the assessment of Loeffler endocarditis. In addition, a summary of the features of hypereosinophilic syndrome and Loeffler endocarditis is provided in tabular form.